Competencia económica en mercados digitales: la experiencia en México - García Santos Coy, Luis Gerardo (2020)
Digital platforms are changing the world, from the way we communicate to the way we commercialize products and services. Antitrust regulators are facing new challenges as they review entirely new and unprecedented markets with particular rules and dynamics. In Mexico, both antitrust authorities (the Federal Economic Competition Commission and the Federal Institute of Telecommunications) have suggested different interpretations regarding a jurisdictional assessment for digital markets, to the extent that it has been necessary to involve Federal Courts. Particularities of multiple-sided markets, big data, indirect network effects, multi-homing and the different conception of market power in digital markets have required a new approximation by antitrust authorities, both regarding merger control and in the investigation and prosecution of anticompetitive behavior.